1996
DOI: 10.1105/tpc.8.8.1353
|View full text |Cite
|
Sign up to set email alerts
|

Preamylopectin Processing: A Mandatory Step for Starch Biosynthesis in Plants.

Abstract: It has been generally assumed that the [alpha]-(1->4)-linked and [alpha]-(1->6)-branched glucans of starch are generated by the coordinated action of elongation (starch synthases) and branching enzymes. We have identified a novel Chlamydomonas locus (STA7) that when defective leads to a wipeout of starch and its replacement by a small amount of glycogen-like material. Our efforts to understand the enzymological basis of this phenotype have led us to determine the selective disappearance of an 88-kD starch hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(83 citation statements)
references
References 37 publications
4
79
0
Order By: Relevance
“…The finding that LD can catalyse transglycosylation reactions may be relevant to the fine control of pre-amylopectin trimming, as postulated by Mouille et al (1996). However, recent work on barley mutants deficient in isoamylase suggested that this activity is more important in starch granule initiation and growth (Burton et al 2002).…”
Section: Discussionmentioning
confidence: 92%
“…The finding that LD can catalyse transglycosylation reactions may be relevant to the fine control of pre-amylopectin trimming, as postulated by Mouille et al (1996). However, recent work on barley mutants deficient in isoamylase suggested that this activity is more important in starch granule initiation and growth (Burton et al 2002).…”
Section: Discussionmentioning
confidence: 92%
“…The participation of phosphorylase in starch biosynthesis could proceed by catalyzing distinct cleavage reactions, similar to the process that has been proposed for hydrolases Mouille et al 1996;van de Wal et al 1998). However, even a polymerizing function cannot be excluded, provided that metabolic channeling alters the eective ratio of orthophosphate to glucose 1-phosphate in the vicinity of the enzyme.…”
Section: Fig 5a±dmentioning
confidence: 93%
“…Consequently, an attractive model for the role of ISA1 and ISA2 in starch biosynthesis is in so-called pre-amylopectin trimming, whereby ISA isoforms trim/remove inappropriately spaced and positioned α-(1→6)-branch linkages that are formed on the surface of the growing granule [331] by the actions of SSs and SBEs. In this model, trimming of α-(1→6)-branch points on such structures by ISAs allows for glucan chains to assemble into a water insoluble structure via the formation of parallel double helices [332], leading to polysaccharide aggregation [333,334]. In this model, loss of ISA1 or ISA2 creates an abundance of branch points leading to unfavourable conditions for the formation of crystalline lamellae, resulting in the less ordered phytoglycogen.…”
Section: Debranching Enzymesmentioning
confidence: 99%